2000
DOI: 10.1038/sj.sc.3101039
|View full text |Cite
|
Sign up to set email alerts
|

Epidural electrical stimulation of posterior structures of the human lumbosacral cord: 2. quantitative analysis by computer modeling

Abstract: Objectives: Analysis of the computed recruitment order of an ensemble of ventral and dorsal root ®bers should enlighten the relation between the position of a bipolar electrode and the observed order of muscle twitches. Material and methods: Thresholds of selected spinal root ®bers are investigated in a two step procedure. First the electric ®eld generated by the electrodes is computed with the Finite Element Method. In the second step the calculated voltage pro®le along each target neuron is used as input dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
164
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 186 publications
(182 citation statements)
references
References 16 publications
(17 reference statements)
7
164
0
Order By: Relevance
“…Quantitative analysis by computer modeling of the epidural electrical stimulation of posterior structures of the human lumbar cord 27 demonstrate actual measurements of relation between stimulus strength, site of stimulation, size and the order of muscle twitches. Thus we have used a functional criteria, in contrast to computer modeling, which is based on computation of electrophysiological parameters of muscle twitches and of dimensions of anatomical structures, electrical properties, electrical ®eld and conducting axons.…”
Section: Discussionmentioning
confidence: 96%
“…Quantitative analysis by computer modeling of the epidural electrical stimulation of posterior structures of the human lumbar cord 27 demonstrate actual measurements of relation between stimulus strength, site of stimulation, size and the order of muscle twitches. Thus we have used a functional criteria, in contrast to computer modeling, which is based on computation of electrophysiological parameters of muscle twitches and of dimensions of anatomical structures, electrical properties, electrical ®eld and conducting axons.…”
Section: Discussionmentioning
confidence: 96%
“…Computer simulation of the epidural electrode setup as used in the present study showed that the largest lumbosacral posterior root fibers entering the cord caudally to the level of the cathode could still be activated by a maximum stimulation voltage of 10 V at a distance of up to 2 cm. 33 Depending on the relative rostrocaudal position of the cathode with respect to a given posterior root fiber, we suggest two different sites of the initiation of afferent volleys in the posterior roots. For cathode positions at upper lumbar cord levels, lumbar posterior root fibers entering the cord in the vicinity of the cathode will have lowest thresholds.…”
mentioning
confidence: 82%
“…Geometric and electric factors result in lowthreshold sites for electrical stimulation where posterior root fibers enter the spinal cord. 18,[31][32][33][34][35] At these sites, posterior root fibers entering the cord caudal to the cathode can have lower thresholds than longitudinal fibers passing the level of the cathode. The high electric conductivity of the cerebrospinal fluid and the longitudinal orientation of the white matter allow the current to spread in a rostrocaudal direction.…”
mentioning
confidence: 99%
“…Monopolar stimulation was carried out by selecting one of the epidural electrodes as cathode and the active area of the implanted pulse generator case ("c") as anode. The pulse generator delivered capacitively decoupled monophasic rectangular constant-voltage pulses of 210-s width, each followed by an exponentially decaying phase to adjust charge balance for each stimulus and avoid delivery of direct current (Rattay et al 2000). Programmable stimulation frequencies and intensities were 2-130 Hz and 0 -10.5 V.…”
Section: Methodsmentioning
confidence: 99%